Biosand Filter for Removal of Organic Pollutant from Laboratory Wastewater. (September 2020) - Primasari, B; Indah, S; Afrianita, R; Rahmatesa, F
Abstract: This research aims to investigate the ability of biosand filter to remove organic pollutants from laboratory wastewater. Biosand filter is a simple treatment using fine sand, coarse sand and gravel media. In the biosand filter, the biofilm growth occurs on the top surface of the media. The observed parameter for organic content was BOD and COD. The media in the biosand filter reactor were fine sand: coarse sand: gravel with a depth ratio of 50: 5: 5 cm. The biofilm growing process was carried out for 15 days by immersing the media with samples. The substrate was added to the reactor in the 10 th day to accelerate biofilm growth. During the growth of the biofilm, the dissolved oxygen (DO), pH and temperature were also observed. After the biofilm growth, the biosand filter was operated intermittently for 14 days, which is an hour operation and a pause period of 47 hours, repeatedly until 29 days. The applied flow rate was 0.6 L / min. The results showed that BOD removal efficiency was 76.9%, and COD removal efficiency was 73.5%. The biosand filter reduced BOD concentration from 161.5 mg/L to 36.1 mg/L and reduced COD concentration from 202.4 mg/L to 52.8 mg/L.